1996
DOI: 10.2307/2096356
|View full text |Cite
|
Sign up to set email alerts
|

Life after Welfare: Women, Work, and Repeat Dependency

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to American Sociological Review. I examine the process by which single mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
190
4
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(205 citation statements)
references
References 33 publications
10
190
4
1
Order By: Relevance
“…(For national studies, see, for example, Harris, 1996;Meyer and Cancian, 1998;and Pavetti and Acs, 1997. For studies in individual states or groups of states, see, for example, Brauner and Loprest, 1999;Friedlander and Burtless, 1995;Loprest, 1999; U.S. Department of Health and Human Services, 1999a,b;U.S. General Accounting Office, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…(For national studies, see, for example, Harris, 1996;Meyer and Cancian, 1998;and Pavetti and Acs, 1997. For studies in individual states or groups of states, see, for example, Brauner and Loprest, 1999;Friedlander and Burtless, 1995;Loprest, 1999; U.S. Department of Health and Human Services, 1999a,b;U.S. General Accounting Office, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Although they do a good job at establishing the work and family predictors of welfare dependency, prospective studies have not typically gathered data on recipients' drinking and drug use. [7][8][9][10][11] Researchers have only been able to speculate about the impact that substance abuse might have on welfare use (e.g., perhaps giving rise to work impairments or to weak incentives for leaving welfare)." 3 The present study, which evaluated alcohol and drug problems in representative samples of welfare recipients followed over a 6-year period, is the first to prospectively examine substance abuse as a determinant of subsequent welfare dependency.…”
mentioning
confidence: 99%
“…Harris (1996) found that a significant proportion of those leaving welfare (most of whom would be single parents) did not remain off welfare for long. One key factor that helped significantly in avoiding welfare "recidivism" was marriage/cohabitation; those who remained single had higher-thanaverage rates of return to welfare.…”
Section: Implications For Conventional Welfare Recipientsmentioning
confidence: 99%